Small cells and the mobile broadband ecosystem - William Lehr; Miquel Oliver (International Telecommunications Society (ITS), 2014)
The growth of mobile broadband and wireless services of all kinds is helping propel the transition toward small cell architectures. This transition has the potential to be as significant for the mobile broadband ecosystem as the transition from mainframes to PCs was for computing. The WiFi and 3G/4G LTE ecosystems highlight two possible directions for small cells. We contrast these ecosystems and explain how the transition to small cells helps drive fixed-mobile convergence, empowers end-users, and facilitates more dynamic spectrum sharing.
Keywords: 330